Remote sensing archaeology: Tracking and mapping evolution in European scientific literature from 1999 to 2015 - Agapiou, Athos; Lysandrou, Vasiliki (My University, 2015)
This paper discusses the on-going research related to remote sensing archaeology in Europe, since the launch in 1999 of the first high resolution satellite sensor IKONOS. During these 16 years, significant technological improvements have been made both in space sensors as well in other non-contact remote sensing technologies, roviding new tools for scientists to search the hidden past. The analysis presented here follows a citation based approach, where useful information is retrieved from the scientific literature. The paper visualises these trends by constructing science maps, based on bibliographic data of established research journals, found in Scopus, ScienceDirect and Web of Science (WoS) search engines. In addition, mapping and clustering analyses were carried out considering the Institutions that applied remote sensing technologies for archaeological purposes, thus providing a better insight and understanding of the current status of remote sensing archaeology in Europe. Time-stamped maps from 1999 until 2015 indicate on one hand that remote sensing technologies are widely accepted and applied by the archaeological community, but at the sametimetheymake clear that substantial gaps still exist amongst European countries. Finally, the popularity of specific terms or the emergence of newterms in scientific literature through time is also presented, providing a synoptic viewof the history and development of the remote sensing archaeology discipline. The discussion section analyses the gaps of the current studymainly due to "missing literature ". The paper underlines the need for the development of a common depository of all knowledge, acquired by the scientists operating in the field worldwide, to improve the " transfer of knowledge " and therefore harmonise the existing gap between the different scientific fields of remote sensing archaeology.
Keywords: Aerial archaeology; Bibliometric; Field spectroscopy; Geophysics archaeology; Remote sensing archaeology; Satellite archaeology